Studi Analisis Keberhasilan Integrasi Pembelajaran Sosiologi Dengan Nilai-Nilai Islam Dalam Membina Karakter Islami - Hidayat, Tatang (JOM, 2024)
Integration of Islamic values in learning can be one of the solutions in the midst of a secular education system that separates religion from life. The purpose of this study is to analyze the success of the integration of Islamic values in sociology learning in fostering Islamic character at SMA PGII 2 Bandung. This research uses a qualitative approach and descriptive method of case study type. The researcher acts as the main instrument. Data collection techniques with interviews, observations, and documentation studies. Data analysis techniques with data reduction, data coding, data display, interpretation of findings and conclusion drawing. Based on the results of the study, the successful integration of Islamic values in sociology learning at SMA PGII 2 Bandung has not been seen as a whole, but only at the level of curriculum integration and partial learning culture. As for the characteristics in the planning and implementation of new sociology learning in the integration stage of justification of sociology material with verses of the Koran. The level of success of the integration program of Islamic values in sociology learning in students is seen from the characters in sociology subjects such as religious, honest, disciplined, responsible, caring (mutual cooperation, cooperation, tolerance, peace), polite, responsive, and pro-active. However, the characters in sociology subjects have not been integrated with Islamic values. Therefore, the character must be integrated with Islamic values so as not to lose value. The goal is that students practice the character in sociology in a fully integrated manner between hablumminallāh and hablumminannās.